(untitled) (Research, Society and Development, 2020)
The objective of this study was to investigate sheep meat: consumption habits, knowledge of producers and consumers about aspects related to animal welfare and the acceptance of certified products. 417 potential sheep meat consumers were interviewed using questionnaires. The interviewees were selected during the 92 Expo Feira de Pelotas and at strategic points of sale of meat such as: butchers, meat boutiques and supermarkets, located in the city of Pelotas. Data analysis was performed using descriptive statistics with frequency distribution being compared using the chi-square test, or the Kruskal Wallis test to compare the means. Of those surveyed, 34% claim to consume sheep meat at least once a month and only 6% declared not to consume this product. Regarding the importance of animal welfare practices, 39% consider that this activity is extremely important, also, 90% said they are concerned about how animals are raised and slaughtered and 87.8% consider it important to learn more about the breeding system before consuming the product. Producers and people of rural origin have a greater knowledge of the rules that govern animal welfare compared to consumers and people of urban origin. Among those interviewed, 90.1% stated that they would buy the product with an animal welfare certification seal and 74.2% would pay more to obtain a guarantee that the animals were raised under animal welfare standards. It is evident that there is concern among the public interviewed about the adoption of animal welfare practices, however, the knowledge of the consumer of sheep meat on this subject is still restricted.